Unraveling the role of hypoxia-inducible factors in cutaneous melanoma: from mechanisms to therapeutic opportunities - Arianna Bellazzo; Barbara Montico; Roberto Guerrieri; Francesca Colizzi; Agostino Steffan; Jerry Polesel; Elisabetta Fratta (Cell Communication and Signaling)
Abstract Hypoxia is a common feature of solid malignancies, including cutaneous melanoma (CM). Hypoxia-inducible factor (HIF)-1α and HIF-2α orchestrate cellular responses to hypoxia and coordinate a transcriptional program that promote several aggressive features in CM, such as angiogenesis, epithelial-mesenchymal transition, metastasis formation, metabolic rewiring, and immune escape. BRAFV600E, which is the most frequent mutation observed in CM patients, usually increases HIF-α signaling not only in hypoxia, but also in normoxic CM cells, enabling HIF-1α and HIF-2α to continuously activate downstream molecular pathways. In this review, we aim to provide a comprehensive overview of the intricate role and regulation of HIF-1α and HIF-2α in CM, with a brief focus on the complex interactions between HIF-α subunits and non-coding RNAs. We also discuss HIF-α-mediated cellular responses in normoxia along with the mechanisms that allow HIF-α subunits to maintain their stability under normal oxygen conditions. Finally, we resume available evidence on potential therapeutic approaches aimed at targeting HIF-1α and/or HIF-2α.